Woman in the Smart Machine Age: The Effectiveness of Intervention Techniques to Overcome Gender Disparities in the Accounting Profession - Christine Desideria Jahi; Cipto Wardoyo; Satia Nur Maharani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Many companies today have used various accounting applications to be able to produce accurate financial statements and analysis. For example, Accurate, Zahir, Jurnal and MYOB. However, the accounting profession has a very important responsibility to manage risks that occur in a company. The task of accountants is also to analyze financial information and assist in making the right decisions by providing complete reports that show the company's real performance. The existence of female accountants in accounting activities that are synonymous with masculine traits and the needs related to how to adapt to new types of accounting that can work in harmony and control technology in the era of digitalization is an important point to assess gender equality and leadership abilities possessed by female accountants. This study uses one group pre-test and post-test design with variables of the use of accounting applications (X) and gender gaps in the accounting profession (Y). The purpose of this study is to see how the use of accounting applications affects the gender gap in the accounting profession. This study used SPSS 24 as a calculation tool. The object of this study is an 8th semester accounting student class of 2019 at State University of Malang. The results of this study show that the use of accounting applications has a significant positive effect on the gender gap in the accounting profession. This shows that there is a strong correlation between the increasing pace of technological development in the era of using accounting applications can affect the gender gap in the accounting profession. This study uses the theory of Cyberfemism which uses new media as a tool to eradicate cybeirfeiminists from male-dominated discourse. The relationship between women and technology is inadequate, easily undermined by society's stigma that technology is very difficult with the desire for technology. The symbolic depiction of theology produces stereotypes where the definition is incapable in the field of theology. Based on the research findings, it can be concluded that the use of accounting applications has a significant positive effect on the geindeir in accounting professions. This means that the development of technology will provide an increase in gender gaps in the accounting profession caused by the lack of representation and support of women in an adequate organization.